Preliminary investigations with adapted rumen microorganisms (ARM) for fattening beef cattle - C.L. Drake; D.L. Good; R.R. Schalles; P.A. Hahn; O.D. Jr. Myrick (Kansas Agricultural Experiment Station Research Reports, 1970)
The use of rumen microorganisms is not new but neither is it a common practice. We used a product developed by W.R. Grace and Company in an attempt to reduce the "adaptation period" of cattle placed on a finishing ration. The adaptation response is believed to correlate with changes in microbial populations in the cattles rumen. Microbes that efficiently metabolize one type of diet, like forage, do not survive on a high grain diet. However, the multitude of microbes in the rumen includes types that help digest grain. When they increase until they dominate the rumen population, the adaptation period is complete.
Keywords: Cattlemen& #x27; s Day; 1970; Report of progress (Kansas State University. Agricultural Experiment Station); 536; Beef; Adapted rumen Microorganisms (ARM); Finishing ration